2014
DOI: 10.1007/s13365-014-0281-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of myeloid cells in HIV-1-host interplay

Abstract: The AIDS Research Field has embarked on a bold mission to cure HIV-1-infected individuals of the virus. To do so, scientists are attempting to identify the reservoirs that support viral persistence in patients on therapy, to understand how viral persistence is regulated and to come up with strategies that interrupt viral persistence and that eliminate the viral reservoirs. Most of the attention regarding the cure of HIV-1 has infection has focused on the CD4+ T-cell reservoir. Investigators are developing tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Findings suggest that in naïve patients, the activated CD4+ T cells accounts for most of plasma viremia (99%) while the other 1% of the virus may be generated primarily from tissue macrophages [ 69 ]. However, in the presence of cART, macrophages are likely the main source of plasma viremia as active viral replication is halted in CD4+ T cells [ 69 , 70 , 71 ]. Furthermore, it has been reported that circulating monocytes are not a major reservoir of HIV-1 in elite suppressors [ 72 ].…”
Section: Hiv-1 Infection Of Monocytes/macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings suggest that in naïve patients, the activated CD4+ T cells accounts for most of plasma viremia (99%) while the other 1% of the virus may be generated primarily from tissue macrophages [ 69 ]. However, in the presence of cART, macrophages are likely the main source of plasma viremia as active viral replication is halted in CD4+ T cells [ 69 , 70 , 71 ]. Furthermore, it has been reported that circulating monocytes are not a major reservoir of HIV-1 in elite suppressors [ 72 ].…”
Section: Hiv-1 Infection Of Monocytes/macrophagesmentioning
confidence: 99%
“…It is worth mentioning that opportunistic pathogens such as Mycobacterium avium and Pneumocystis carinii activate the macrophages and induce HIV production from infected macrophages in lymph nodes [ 81 , 82 ]. These findings suggest that macrophages can be a prominent source of viremia at later stages of HIV when lymphoid tissues are quantitatively and qualitatively impaired and opportunistic pathogens fuel HIV pathogenesis by activating and increasing the viral production from infected macrophages [ 40 , 71 , 81 , 82 ]. In addition, T cells also induce HIV-1 replication in myeloid cells.…”
Section: Hiv-1 Infection Of Monocytes/macrophagesmentioning
confidence: 99%
“…HIV infects myeloid cells in lymph nodes, spleen, heart, lungs, the peripheral nervous system, and the central nervous system (CNS) ( 7 11 ). The HIV genome encodes genes that specifically interact and/or interfere with restriction factors present in myeloid cells, providing evolutionary evidence that HIV replication in myeloid cells is important for virus replication and pathogenesis in vivo ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…HIV-infected macrophages are one such cell type worth consideration and several excellent reviews have recently elaborated on this subject (Costiniuk and Jenabian, 2014; Dey et al , 2012; Stevenson, 2014; Tan and Sattentau, 2013; Watters et al , 2013). Infected macrophages have been found at low but measurable frequencies in lung and duodenal tissue of patients on ART with undetectable plasma virus (Cribbs et al , 2015; Zalar et al , 2010) and in brain tissues of SIV-infected macaques on ART (Clements et al , 2002).…”
mentioning
confidence: 99%
“…Macrophages support HIV infection without undergoing viral cytolysis or apoptosis and infected cells are insensitive to the currently available antiretroviral drugs and antiviral CTL; as a consequence infected macrophages have long life span compared to productively infected T cells (Borjabad et al , 2011; Busca et al , 2012; Cribbs et al , 2015; Le Douce et al , 2010; Murphy et al , 2008; Vojnov et al , 2012). Both HIV and SIV have evolved strategies to overcome macrophage restriction factors, contributing to their persistence in these cells (reviewed in (Stevenson, 2014)). The ability of HIV to assemble and accumulate in intracellular compartment connected to extracellular space (reviewed in (Tan and Sattentau, 2013)) may further protect virus from immunological responses and contribute to virus transmission despite ART (Duncan et al , 2013).…”
mentioning
confidence: 99%